MAKE AN IMPRESSION IN 60 SECONDS: VIDEO ON SOCIAL MEDIA, THE MAIN WEAPON OF PROFESSIONAL MARKETERS – TRENDS 2023 - Hilda (Acta Informatica Malaysia)
In the era of ever-changing marketing, video on social media has become the main weapon for professional marketers in reaching their audience. This research analyzes the latest trends and practices in video marketing, with a focus on social media platforms, as an effective marketing strategy. Findings show that short, visually appealing videos and audio are the top choice, followed by explainer videos and testimonials from new users. The importance of variation in the types of videos used is also emphasized. However, several issues, such as the lack of detail about the research methodology and the need for a more in-depth analysis of video marketing options on social media, need to be addressed. From a Theory of Marketing perspective, these findings are consistent with basic marketing concepts, such as the exchange of information between sellers and consumers, the importance of informative and educational content, and the role of trust and involvement in influencing consumer behavior. Thus, this research not only provides insight into video marketing trends but also validates the relevance of fundamental concepts in marketing that have been discovered by marketing theory. Through a deep understanding of the latest trends and practices in video marketing, as well as the application of basic marketing principles, marketing practitioners can increase the effectiveness of their campaigns and better achieve marketing goals in the ever-evolving digital era.